2018
DOI: 10.1002/adsc.201800138
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Sequential C(sp2)‐H Alkynylation/Annulation of 2‐Phenylphenols with Haloalkynes Using Phenolic Hydroxyl as the Traceless Directing Group

Abstract: An efficient, palladium(II)-catalyzed, C(sp 2 )-H alkynylation/annulation of 2-phenylphenols with haloalkynes for the synthesis of substituted 6-methylene-6H-dibenzo [b,d]pyrans is reported. This protocol features a traceless directing group strategy, unique regioselectivity and mild reaction conditions. Significantly, preliminary mechanistic studies suggest that the sequential C(sp 2 )-H alkynylation and annulation reaction could be involved in the transformation procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Heteroaromatics such as pyridine and thiophene were not affected by the reaction conditions (Figure 1, 11 and 12). We next evaluated the scope of terminal aliphatic alkynes and found that at lower temperatures (À25 C) the reaction showed high trans-selectivity 62 (Figure 1 Haloalkynes are versatile, yet readily available, building blocks, 46,47,[63][64][65][66][67][68][69] with which our highly regioselective iodochlorination protocol should enable to access extremely valuable trihalogenated alkenes. 70 To our delight, both aromatic and aliphatic haloalkynes gave excellent regioselectivity and chemical yields of trihalogenated alkenes.…”
Section: Resultsmentioning
confidence: 99%
“…Heteroaromatics such as pyridine and thiophene were not affected by the reaction conditions (Figure 1, 11 and 12). We next evaluated the scope of terminal aliphatic alkynes and found that at lower temperatures (À25 C) the reaction showed high trans-selectivity 62 (Figure 1 Haloalkynes are versatile, yet readily available, building blocks, 46,47,[63][64][65][66][67][68][69] with which our highly regioselective iodochlorination protocol should enable to access extremely valuable trihalogenated alkenes. 70 To our delight, both aromatic and aliphatic haloalkynes gave excellent regioselectivity and chemical yields of trihalogenated alkenes.…”
Section: Resultsmentioning
confidence: 99%
“…56 In 2018, the Rovis group reported an iridium-promoted double C-H bond activation of anisoles with difluoroalkynes to afford chromenes (Scheme 12d). 57 Biphenyl-2-ols were used utilized by both the Jiang and Lam groups and coupled with haloalkynes under palladium catalysis 58 or 1,3-enynes under rhodium catalysis, 59a respectively, to give 6H-benzo [c]chromenes (Scheme 12e and 12f). It was noteworthy the corresponding alkynes contributed as a one-carbon source this time.…”
Section: Chromenes and Isochromenesmentioning
confidence: 99%
“… 177 Inspired by this work H. Jiang et al reported a Pd-catalysed sequential C–H alkynylation/annulation of 2-phenylphenols with haloalkynes. 178 Interesting examples are reported for the synthesis of coumarins via ortho -substitution of phenols with alkynoates initiated by an ortho -palladation. Indeed, treatment of alkynoates with electron-rich phenols in the presence of a Pd-catalyst and an acid does generate coumarins.…”
Section: Introductionmentioning
confidence: 99%